Use of egg custard augmented with cod liver oil and Moina micrura on production of freshwater prawn postlarvae - Alam, M. J.; Ang, K. J.; Begum, M. (Springer, 1995)
Use of egg custard augmented with cod liver oil (CLO) fed during the day, and of an overnight feed with Moina micrura, were evaluated in terms of its effects on production of freshwater prawn (Macrobrachium rosenbergii) postlarvae (PL). Four levels of CLO (0, 1,3 and 5%) were tested. Significantly higher mean (sd) productions, ranging from 11.27 (1.16) to 13.02 (1.70) PL l−1, were obtained for larvae fed egg custard enriched with CLO compared with that of 7.83 (1.58) PLl−1 for larvae fed egg custard without CLO. The development and survival of larval stages were also higher for the CLO diets. The ω-3 highly unsaturated fatty acid (HUFA) in egg custard increased with increasing CLO level (0–5%). The fatty acid composition of postlarvae reflected the composition of the diet.